A154: Glucocorticoid Therapy and the Risk of Incident Vertebral Fracture in Children with Rheumatic Disorders. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - LeBlanc, Claire M. A.; Ma, Jinhui; Scuccimarri, Rosie; Cabral, David A.; Dent, Peter B.; Ellsworth, Janet E.; Houghton, Kristin; Huber, Adam M.; Jurencak, Roman; Lang, Bianca A.; Larche, Maggie; Lentle, Brian; et al.
Abstract : Background/Purpose: To determine the incidence of vertebral fracture (VF) in the three years following glucocorticoid (GC) initiation, and the effect of GC on the risk of incident VF in children with rheumatic disorders (RD). Methods: Children with RD were enrolled within 30 days of GC initiation and followed for 3 years, with VF assessed at baseline and then annually using the Genant method on lateral spine radiographs. An incident VF was defined as a new fracture in a previously normal vertebral body or worsening of an existing VF. The annual and the 3 year cumulative incidences were calculated as the number of new cases divided by the number of subjects who completed VF assessment at the specified time periods. Six different time‐dependent GC exposure measures were constructed: cumulative dose, average daily dose, duration on GC therapy, dose intensity (cumulative dose divided by duration on GC therapy) over 3 years, recent average daily dose and duration on GC therapy over the preceding 12 months. Extended Cox's models were used with alternative time‐dependent variables, adjusting for factors at baseline including age, gender, body mass index, vitamin D and calcium supplementation, disease activity, bone mineral density, physical activity, and presence of prevalent VF. Results: 136 enrolled children (mean ± SD age 9.9 ± 4.4 years, 65% girls) held the following diagnoses: 22% juvenile dermatomyositis (JDM), 21% non‐systemic juvenile idiopathic arthritis (JIA), 19% systemic lupus erythematosus (SLE), 18% systemic JIA, 12% systemic vasculitis, and 9% other RD. 9 children had VF at baseline (3 JDM, 2 systemic JIA, 2 SLE, 1 systemic vasculitis, 1 localized scleroderma), with an estimated prevalence of 6.6% (95% confidence interval (CI) 2.4–10.8%). 18 incident VF were identified in 15 children during the 3 years following GC initiation (6 JDM, 4 SLE, 2 systemic vasculitis, 2 systemic JIA, and 1 non‐systemic JIA). The 3‐year cumulative VF incidence was 13.0%, at a rate of 4.9 per 100 person‐years. Of the 18 incident VF events, 7 occurred during the first year at an annual incidence of 6.0% (95% CI 1.7–10.3%); 6 VF occurred during the second year (annual incidence 5.6%; 95% CI 1.2–9.9%); 5 VF occurred during the third year (annual incidence 4.3%; 95% CI 1.0–8.1%). 64% of patients had mild incident VF as the worst grade, 36% had moderate fractures, and none had severe fractures. Of those with incident fractures, 21% had no complaints of back pain in the preceding 12 months. Multivariable models showed that every 100 mg/kg increase in cumulative GC dose was associated with a 30% increased incident VF risk (hazard ratio (HR) = 1.3, 95% CI 1.1, 1.6). Every 0.5mg/kg increase in average daily dose over the 3 year period was associated with a 4.2 fold increased VF risk (HR = 4.2, 95% CI 2.3, 7.7), and every 0.5 mg/kg increase in daily dose during the preceding 12 months was associated with a 2.7 fold increased incident VF risk (HR =2.7, 95% CI 1.3, 5.2). Conclusion: We have shown that 13.0% of children with RD sustained VF within three years followingGC initiation, of which 36% had moderate fractures. Cumulative dose, average daily GC dose, and recent average daily GC dose were associated with a significantly increased VF risk. Funded by CIHR FRN 64285